Nicotinic Acetylcholine Receptor Clusters Localization On Lipid Domains Of The Plasmalemma - Kamerbeek, Constanza Belén (2011)
In the present work we have attempted to establish whether there is a correlation between antibody-induced nicotinic acetylcholine receptor (AChR)-rich clusters and the physical state of the underlying cell membrane in living cells. For this purpose di-4- ANEPPDHQ, a fluorescent probe that differentiates liquid-ordered from liquid-disordered phases in model membranes was used in combination with labeling of the AChR in CHO-K1/A5, a clonal cell line expressing adult muscle-type AChR. The so-called generalized polarization (“GP”) of di-4-ANEPPDHQ was measured in regions of the cell-surface membrane associated with the AChR platforms clearly identified using conventional widefield fluorescence microscopy. Under control conditions AChR clusters are roughly equally distributed among liquid-ordered and liquid-disordered domains. This distribution changes upon cyclodextrin-mediated cholesterol depletion or by Latrunculin disruption of the actin cytoskeleton. Association of AChR clusters with lipid domains with different biophysical properties may have consequences on AChR trafficking processe.